2016
DOI: 10.1371/journal.pone.0168367
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Gene zinc finger protein 3(ZFP3) Is Involved in Salt Stress and Osmotic Stress Response

Abstract: Plants are continuously challenged by various abiotic and biotic stresses. To tide over these adversities, plants evolved intricate regulatory networks to adapt these unfavorable environments. So far, many researchers have clarified the molecular and genetic pathways involved in regulation of stress responses. However, the mechanism through which these regulatory networks operate is largely unknown. In this study, we cloned a C2H2-type zinc finger protein gene ZFP3 from Arabidopsis thaliana and investigated it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…Although many C2H2 transcription factors show transcriptional activation activity, there is no general rule about particular domains that function as transcriptional activators among the various types of domains, such as proline-rich, serine-rich, glutamine-rich, and threonine-rich domains (De Pater et al, 1996;Kiełbowicz-Matuk, 2012;Tang et al, 2019). Many C2H2type zinc finger proteins function as transcriptional activators during plant growth and abiotic stress, but the activation domain is poorly understood (Sakamoto et al, 2000;Xu et al, 2007;Zhou et al, 2011;Zhang et al, 2016a). Several stress-related C2H2-type zinc finger proteins contain a proline-rich region between the NLS and L-box motifs, which is considered to be the activation domain (Sakamoto et al, 2000).…”
Section: Transcriptional Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many C2H2 transcription factors show transcriptional activation activity, there is no general rule about particular domains that function as transcriptional activators among the various types of domains, such as proline-rich, serine-rich, glutamine-rich, and threonine-rich domains (De Pater et al, 1996;Kiełbowicz-Matuk, 2012;Tang et al, 2019). Many C2H2type zinc finger proteins function as transcriptional activators during plant growth and abiotic stress, but the activation domain is poorly understood (Sakamoto et al, 2000;Xu et al, 2007;Zhou et al, 2011;Zhang et al, 2016a). Several stress-related C2H2-type zinc finger proteins contain a proline-rich region between the NLS and L-box motifs, which is considered to be the activation domain (Sakamoto et al, 2000).…”
Section: Transcriptional Activationmentioning
confidence: 99%
“…In addition, IbZFP1 in sweet potato (I. batatas (L.) Lam.) (Wang et al, 2016), ZFP3 (Zhang et al, 2016a), and AtSIZ1 in Arabidopsis enhance plant salt tolerance by increasing proline biosynthesis and accumulation.…”
Section: Roles In Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies addressing plant cell responses to salt stress focus on the 86 regulation of ion channels, such as by manipulating the expression and activity of the 87 plasma membrane Na + /H + antiporter SOS1 to remove sodium from the cytosol (Yang 88 et al, 2009;Quintero et al, 2011). Other investigators have found that altered gene 89 expression patterns facilitate plant cell growth under salt stress (Xu et al, 2015; 90 Bahieldin et al, 2016;Zhang et al, 2016). For example, the expression levels of 91 glycosyltransferases UGT79B2 and UGT79B3 are strongly induced by high salinity, 92 which lead to the accumulation of anthocyanins and plant yield that reflects salt-stress 93 tolerance .…”
mentioning
confidence: 99%
“…In this study, using 97 Arabidopsis C2H2-ZFP sequences as a query, we identified 104 C2H2-ZF family members in the tomato genome, which contains at least one C2H2-ZF motif (X2-Cys-X(2-4)-Cys-X12-His-X(3-5)-His), and the lengths of these sequences varied from 96 to 1,178 amino acid residues, with striking distinctions (Table S2), suggesting that a high degree of complexity among the tomato C2H2-ZFs (Liu et al, 2015). The 'QALGGH' motif was almost invariant in the tomato C2H2-ZFPs ( Figure 2); however, the C2H2-ZFP subfamilies in other plant species have previously been defined based on changes to the conserved "QALGGH" motif (Fedotova et al, 2017;Liu et al, 2015;Razin et al, 2012;Takatsuji, 1999;Wei et al, 2016;Yuan et al, 2018;Zhang et al, 2016). In this study, to reveal phylogenetic relationship of tomato C2H2 family members, 104 C2H2-ZFPs were divided into nine major groups according to the NJ phylogenetic tree ( Figure 1B), which were well consistent with arrangements, numbers, and types of their C2H2-ZF domains (Figure 2).…”
Section: Discussionmentioning
confidence: 99%